The Factors affecting towards on the need to access funding of the SME Promotion Fund of small and medium-sized business Entrepreneur in Nan District, Luang Prabang Province - liyakhet, kinsavanh; LIYAKET, khinsavanh; HOONGSENGPHA, Soudtida; INDAVONG, dalounny (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The objectives of this research were to study the condition of Accessibility to funding sources of the Small and Medium Enterprises (SMEs) Promotion Fund of small and medium business entrepreneurs in Nan District, Luang Prabang Province, to study the perceptions of small and medium business entrepreneurs towards on the funding source of the Small and Medium Enterprises (SMEs) promotion fund, and to analyze the factors affecting the need to access funding sources of SMEs Promotion Fund of small and medium business entrepreneurs in Nan District, Luang Prabang Province. The research was conducted by using a questionnaire as an instrument for collecting data from 150 SMEs executives/ Entrepreneurs in the Nan district of Luang Prabang Province. The Cronbach alpha reliability coefficient was 0,918. The statistics used for data analysis were frequency, percentage, mean, standard deviation, Binary Regression analysis. The results revealed that: The condition of Accessibility to funding sources of the Small and Medium Enterprises (SMEs) Promotion Fund in Nan District, Luang Prabang Province was the most of the business operations were organized as individual enterprises, invest in the commercial sector, distributed in the domestic market, the number of workers employed was 1-5 people, the business has an average monthly income of less than 50 million kip, the source of working capital was from the business owner's capital, were businesses that didn’t have access to funding sources, could be access to funding was from borrowing family and friends, the purpose of borrowing was to use as working capital in business operations, there was need to access funding sources from small and medium enterprise promotion funds and wanted at more Level. The business found problems in accessing funding from the SMEs Promotion Fund at a moderate level, which was a problem related to the internal business and economic problems were found at a high level. The perceptions of entrepreneurs towards the funding source of the Small and Medium Enterprises (SMEs) promotion fund was at a low level of awareness and understanding of the SME promotion fund (2,49) regarding the objectives and goals of the fund's operation and the terms and conditions of the fund's lending. the factors positively affected the need to access funding sources of SMEs Promotion Fund of small and medium business entrepreneurs in Nan District, Luang Prabang Province was the Business management factor, and the negatively affected were the environmental factor, regulatory factor of financial institutions at a statistical significance 0,05 level.